Ordering of lipid membranes altered by boron nitride nanosheets. Issue 6 (4th December 2017) - Zhang, Yonghui; Li, Zhen; Chan, Chun; Ma, Jiale; Zhi, Chunyi; Cheng, Xiaolin; Fan, Jun
Abstract : Boron nitride nanosheets are novel promising nanomaterials with a lower cytotoxicity than graphene making them a better candidate for biomedical applications. Abstract : Boron nitride nanosheets are novel promising nanomaterials with a lower cytotoxicity than graphene making them a better candidate for biomedical applications. However, there is no systematic study on how they interact with cell membranes. Here we employed large scale all-atom molecular dynamics simulations to provide molecular details of the structure and properties of membranes after the insertion of boron nitride nanosheets. Our results reveal that the boron nitride nanosheet can extract phospholipids from the lipid bilayers and is enveloped by the membrane. Afterwards, the acyl chains of lipid molecules re-orient and become more ordered. As a result, a fluid to gel phase transition occurs in the 1, 2-dimyristoyl- sn-glycero -3-phosphocholine bilayer. Consequently, the bending moduli of the bilayers increase, and the diffusivity of the individual lipid molecule decreases. These changes will affect relevant cellular activities, such as endocytosis and signal transduction. Our study provides novel insights into the biocompatibility and cytotoxicity of boron nitride nanosheets, which may facilitate the design of safer nanocarriers, antibiotics and other bio-nanotechnology applications.